THE EFFECT OF TECHNOLOGY USE IN LECTURER LEARNING IN THE CLASSROOM ON STUDENT LEARNING MOTIVATION: A LITERATURE REVIEW - Yamolala Zega (INJOSEDU: International Journal of Social and Education, 2025)
The effect of lecturers' use of technology in the classroom on students' motivation to learn refers to the extent to which the integration of technological tools and methods by lecturers can change the level of engagement, participation and encouragement that students feel in the learning process. Technology in this context includes various digital tools and platforms such as computer-based presentations, educational applications, online discussion forums, learning videos, and other interactive media used to support classroom teaching. The aim is to provide a more engaging, interactive and effective learning environment, so as to increase students' interest and motivation to learn. This influence can be positive, such as increased participation and understanding of the material, but it can also be negative if the use of technology is not well managed, such as causing distraction or passivity in learning. The results show that the integration of technology in teaching has the potential to increase student engagement and participation, which positively affects their motivation to learn. Technology tools such as interactive presentations, online discussion forums, and multimedia-based learning applications allow for a more dynamic and interactive learning environment.